DISTRIBUSI DALAM EKONOMI ISLAM Upaya Pemerataan Kesejahteraan Melalui Keadilan Distributif - Nahdya Alfaina Karem; Yuliani Yuliani; Binti Mutafarida (JURNAL ILMIAH NUSANTARA, 2024)
Economic inequality is a common challenge faced by various modern economic systems. Unfair income and wealth disparities are the root of the problem of poverty. The development of thinking about distributive justice in Islamic economics was triggered by the realization that existing economic theories were not fully able to overcome the problems of poverty and inequality. Therefore, the study of distribution becomes an important focus in the context of Islamic economics. This article discusses the concept of distribution from an Islamic economic perspective, examines issues of injustice in the Indonesian distribution system, provides a critique of capitalist economic distribution, and ends with a presentation of how Islamic economics supports distributive justice and distribution mechanisms as a solution to achieving justice and social welfare.